Соціальні наслідки пандемії COVID-19 у контексті суспільної трансформації в Україні: соціологічний підхід (за матеріалами наукової доповіді на засіданні Президії НАН України 14 квітня 2021 р.) - Степаненко, В.П. (Вісник НАН України, 2021)
У статті представлено соціологічні підходи до соціальної проблематики
COVID-19 на основі огляду та узагальнення проміжних результатів дослідницького проєкту Інституту соціології НАН України. Обґрунтовано
необхідність формування вітчизняної соціології пандемії як актуального
напряму в корпусі сучасних епідеміологічних досліджень. Окреслено виклики та можливості нового соціального досвіду в Україні в чотирьох соціальних вимірах: соціально-структурному, суспільно-політичному, соціально-психологічному та соціокультурному. Досліджено актуальні аспекти біополітики, проблематику соціальних та суспільно-психологічних ризиків
пандемії. Розглянуто особливості коронавірусної кризи в Україні, зумовлені
її поєднанням зі складними викликами суспільної трансформації, а також
з гуманітарними наслідками окупації АР Крим і поточного військового конфлікту на Донбасі. The COVID-19 pandemic in its global and distant consequences is making changes in various spheres of social reality,
particularly through the transformation of social communication, the changes in social stratification, social-psychological
attitudes and in forming the new rules of socio-biological security. The article presents sociological approaches to the
social issues of COVID-19 based on the overview of intermediate results of the research project by the Institute of Sociology
of the NAS of Ukraine. It is argued that there is the need for the sociology of pandemic as an actual direction in the
framework of contemporary epidemiological research. The challenges and possibilities of new social experience in
Ukraine are characterized in four social dimensions, namely: social-structural, social-political, social-psychological and
social-cultural. Actual aspects of biopolitics, the issues of social and psychological risks of the pandemic are examined.
The peculiarities of the coronavirus crisis in Ukraine are articulated. They are due to the combination of the global pandemic
and complex challenges of Ukraine’s social transformation which is aggravated with humanitarian consequences
of the occupation of the Crimea by Russia and ongoing military conflict in Donbas. It is argued that the social consequences
of the COVID-19 pandemic in Ukraine might manifest themselves in two ways: either as a negative catalyst that
exacerbates the issues of incomplete social transformation or as a kind of “leveler”, that is the factor due to which the
values of mutual social security and new rules of tolerant coexistence will prevail.